TRUTH DAN POST TRUTH DALAM PERSPEKTIF AL-KINDI PADA ERA MILENIAL (MEDIA SOSIAL) - Cika Anugrah Septiyadi; Zahrotul Khafifah; Adesilvi Saisatul Khumairoh; Achmad Fauzan Hidayatullah (Universitas Muhammadiyah Surakarta, 2021)
People have desires to search for the truth and to have broad knowledge. The internet, which was once considered as one of the media to find accurate sources of information, now has become a source of less accurate news. So there needs to be a filter in consuming news from the internet. The purpose of this study is to look at the spread of hoax news because of the lack of awareness. The majority of social media users in the current era do not have an ethical foundation in using their right to express their opinions properly which result in hoaxes. We use literature review method to collect all the information required. In the end, we conclude that people must give an opinion by thinking about the truth first of what they have conveyed. From the truth, it can be understood that something must be justified. In accordance with the truth meant by Al-kindi that in seeking truth must to find the main source of the source itself.